Strategy For Increasing The Competence and Capability of Financial Literacy of MSMEs - Lenggogeni, Lenggogeni; Usman, Bachtiar (International Journal of Advanced Multidisciplinary, 2023)
In its efforts to promote financial inclusivity, the Indonesian government has set a goal of achieving a 75% inclusion rate by 2019. However, as accessibility to formal financial services becomes more convenient for the general population, the risks within the financial industry also escalate. Unfortunately, ordinary individuals are ill-prepared for these circumstances as their understanding of financial products remains limited. The primary issues at hand are twofold: firstly, the lack of financial literacy among micro, small, and medium enterprises (MSMEs) and housewives in Indonesia, and secondly, the need for effective strategies to enhance financial literacy among MSMEs and housewives specifically in UMKM Azalea, located in West Jakarta. PKM aims to deliver training, knowledge, and solutions while offering capital resources. The research methodology employed is a descriptive qualitative approach. The outcomes of PKM reveal that there is a significant deficiency in financial literacy among Azlea MSMEs and households, with only 50% possessing adequate knowledge. Strategies for enhancing competency and capability encompass various aspects, including: a) fostering awareness and understanding of diverse financial products and services, b) comprehending the risks associated with financial products, c) ensuring customer protection, and d) cultivating skills in financial management.